Chestnut shell aqueous extract as a green efficient corrosion inhibitor for acid-cleaning carbon steel - Ceshen Zhou; Taoyu Zhou (PLoS ONE, 2026)
As a new candidate for green corrosion inhibitor as well as a new application of a common food residues for waste resource recycling, an aqueous extract of chestnut shells (ECS), from a discarded item CS ( chestnut shells ) of a daily food chestnut, is investigated and evaluated using multi-means. For the ECS sample itself, UV-visible absorption result reveals its π → π * transition of electrons similar to isoflavonoid; an orthogonal array with four factors is used to optimize the optimal combination of CS dosage, alcohol dosage, temperature, and pH for its preparation, providing the result of “CS 20g/L, ethanol 20% (v/v), 50 o C, and pH 9”. For the ECS sample used as corrosion inhibitor for carbon steel in 1mol/L HCl solution, the Tafel curve of electrochemical polarization demonstrates its mixed-type corrosion inhibition performance dominated by anodic control. Electrochemical impedance spectroscopy ( EIS ) data indicates that a high resistance adsorption barrier film formed by ECS dominates a combined contribution of the film resistance and charge transfer resistance to the corrosion inhibition of carbon steel. Both the Tafel and EIS data achieve an acceptable inhibition efficiency of around 80% for ECS alone at a concentration of 56.6mL/L. Specially important for practical applications, the ECS-induced weight-loss gives an actual-simulated corrosion rate inhibited to around 1.21mm/y, which well meets the 2.23mm/y as limit requirement of the national standard. Furthermore, the ECS-adsorbed process is discussed through adsorption isotherms that follows Temkin model and the model fitting result estimates a change of −27.13kJ/mol in the standard free energy of adsorption, indicating the existence of a mixed process of physi- and chemi-sorption of the ECS on the steel surface. This work highlights the ECS considerable potential for title application namely acid-corrosion inhibition of carbon steel equipment.